A confirmatory examination of age‐associated personality differences: Deriving age‐related measurement‐invariant solutions using ant colony optimization. Issue 6 (8th March 2018) - Olaru, Gabriel; Schroeders, Ulrich; Wilhelm, Oliver; Ostendorf, Fritz
Abstract: Objective: The goal of this study was to examine age‐associated personality differences using a measurement‐invariant representation of the higher‐order structure of the Five‐Factor Model. Method: We reanalyzed the German NEO‐PI‐R norm sample ( N  = 11, 724) and applied ant colony optimization in a multigroup confirmatory factor analysis setting in order to select three items per first‐order factor that would optimize model fit and measurement invariance across 18 age groups ranging from 16 to 65 years of age. Results: Ant colony optimization substantially improved absolute and relative model fit under measurement invariance constraints. However, the results showed that even when selecting items, measurement invariance across a large age span could not be guaranteed. Strong measurement invariance for Extraversion and Agreeableness could not be established. The age‐associated mean‐level differences of the first‐order factors of Neuroticism and Conscientiousness supported the maturity hypothesis. The mean levels of the first‐order factors of Openness varied substantially from each other across age. Conclusions: Findings on age differences in personality can be particularly distorted in older age groups. Testing for and ensuring measurement invariance with item selection procedures can help solve this problem. The higher‐order structure of personality should be accounted for when personality development is examined.